Assessment of drug-loaded nanoparticles in a 3D in vitro brain tumour model - Ivanov, Delyan Pavlov (2015)
This work describes the creation of a three-dimensional model of the children’s brain tumour medulloblastoma using primarily human cells. This in vitro cell culture model was created as a platform for testing novel drug delivery systems for local delivery in the brain. The aim of the local delivery strategy was to reduce radiotherapy through the use of nanoparticle-based chemotherapy. The nanoparticles would be delivered after surgery in the cavity left by the excised tumour tissue. The model was intended to evaluate the selective cytotoxicity of advanced drug delivery systems towards tumour tissue and the benefit of nanoparticle therapy compared to free drug. Normal tissue was modelled using human foetal brain tissue and tumour tissue was represented by a variety of medulloblastoma cell lines. Both were cultured as three-dimensional spheroids free of artificial matrix in ultra-low attachment plates. The tumour and normal cells could be cultured either separately or together and the viability for each cell population determined using a battery of methods. Co-cultures of both cell types had the additional benefit of mimicking the interaction between normal and tumour tissue. The use of physiologically relevant single and co-culture in vitro models could provide information on the relative safety and efficacy of novel brain tumour treatments. The high-throughput platforms used, the algorithms and the validation of a battery of tests in 3D may be extrapolated to other cancer models as well. Moreover the universal marking procedure employed can be employed to label, culture and analyse any two cell types, while preserving tissue heterogeneity and viability. The key benefit from this thesis is the framework for designing in vitro models of tumours that include normal tissue as an internal control. This is an important contribution that can substantiate IC50 values by putting them in the context of drug safety and efficacy. It also highlights the minimum checks and feasibility experiments that need to be done before an in vitro assay is accepted for 3D spheroids.